2015
DOI: 10.1039/c5fo00174a
|View full text |Cite
|
Sign up to set email alerts
|

Health properties of oca (Oxalis tuberosa) and yacon (Smallanthus sonchifolius)

Abstract: Andean roots and tubers are underexploited crops; many contain compounds beneficial to health, so a greater knowledge of their properties is important for encouraging their consumption. The aim of this work was to study the content of bioactive compounds of yacon and oca and their effect on intestinal health using as a model rats of the Wistar strain. Two varieties of ocas (Overa and Rosada) and yacon, which contain significant amounts of fructooligosaccharides and phenolic compounds, were chosen. Rats of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Another study observed that intake of YF (80 g kg −1 FOS) improved the antioxidant capacity of healthy Wistar rats as evidenced by an increase in the content of phenolic components in the cecum. 43 Thus, because cellular damage by ROS is one of the main drivers of mutations, 44 cancer should be considered a disease with highly oxidative characteristics. This highly oxidative state of cancer may explain why YF did not change the TAC in animals with induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study observed that intake of YF (80 g kg −1 FOS) improved the antioxidant capacity of healthy Wistar rats as evidenced by an increase in the content of phenolic components in the cecum. 43 Thus, because cellular damage by ROS is one of the main drivers of mutations, 44 cancer should be considered a disease with highly oxidative characteristics. This highly oxidative state of cancer may explain why YF did not change the TAC in animals with induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the TAC of the plasma was reduced in groups with induced CRC (groups C and CY) and YF treatment was not able to decrease the oxidative damage caused by the carcinogenesis. Another study observed that intake of YF (80 g kg −1 FOS) improved the antioxidant capacity of healthy Wistar rats as evidenced by an increase in the content of phenolic components in the cecum 43 . Thus, because cellular damage by ROS is one of the main drivers of mutations, 44 cancer should be considered a disease with highly oxidative characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Unsold Oca tubers are used for compost. Several studies have analyzed the nutritional characteristics [ 2,3 ] and the starch properties [ 4,5 ] of Oca tubers. These authors [ 2–5 ] report higher values of Vitamin C (30.4−44.8 mg 100 g −1 ), phenolic compounds (149−200 mg AG 100 g −1 ), and anti‐radical activity expressed as vitamin C equivalent (81−128 mg AA 100 g −1 ) in the pulp and peel of Oca tubers (wet basis), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic syndrome (SM) is defined as the set of cardiovascular risk factors constituted by central distribution obesity, Atherogenic dyslipidemia, glucose metabolism abnormalities and arterial hypertension, closely associated with insulin resistance [3,10]. The metabolic syndrome is a major and growing public health clinical challenge throughout the world following urbanization, surplus energy consumption, increased obesity and sedentary lifestyle habits [7].…”
Section: Introductionmentioning
confidence: 99%